2006
DOI: 10.1051/gse:2006020
|View full text |Cite
|
Sign up to set email alerts
|

Sequence heterogeneity and phylogenetic relationships between thecopiaretrotransposon inDrosophilaspecies of therepletaandmelanogastergroups

Abstract: -Although the retrotransposon copia has been studied in the melanogaster group of Drosophila species, very little is known about copia dynamism and evolution in other groups. We analyzed the occurrence and heterogeneity of the copia 5'LTR-ULR partial sequence and their phylogenetic relationships in 24 species of the repleta group of Drosophila. PCR showed that copia occurs in 18 out of the 24 species evaluated. Sequencing was possible in only eight species. The sequences showed a low nucleotide diversity, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…1990 ; Clark et al. 1994 ; Robertson and Zumpano 1997 ; Kordis and Gubensek 1998 ), but in the last two decades, the number of HTTs described in invertebrates, vertebrates and plants, and between species from different higher taxa or realms has increased considerably (e.g., Silva and Kidwell 2000 ; De Almeida and Carareto 2006 ; Diao et al. 2006 ; Ludwig et al.…”
Section: Introductionmentioning
confidence: 99%
“…1990 ; Clark et al. 1994 ; Robertson and Zumpano 1997 ; Kordis and Gubensek 1998 ), but in the last two decades, the number of HTTs described in invertebrates, vertebrates and plants, and between species from different higher taxa or realms has increased considerably (e.g., Silva and Kidwell 2000 ; De Almeida and Carareto 2006 ; Diao et al. 2006 ; Ludwig et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies done have involved the analysis of sequences of transposable elements ( e.g. , mariner, Hosimary, gypsy, copia and micropia ) in species of the two groups (Maruyama and Hartl, 1991; Lawrence and Hart1, 1992; Brunet et al , 1994, 1999; Jordan and McDonald, 1998; Heredia et al , 2004; de Almeida and Carareto, 2006; Ludwig and Loreto, 2007; Ludwig et al , 2008; Vidal et al , 2009; de Setta et al , 2009, 2011; Deprá et al , 2010). These studies found similarities between the sequences of transposable elements from the subgenus Zaprionus and from certain species of the subgroup melanogaster that were greater than the similarities between species of the same species group.…”
Section: Introductionmentioning
confidence: 99%